Comparative study of nonabsorbable and absorbable barrier membranes in periodontal osseous defects by guided tissue regeneration - Shalini Kaushal; Avadhesh Kumar; M.A. Khan; Nand Lal (Elsevier, 2016)
Background: Periodontal invasion of furcation area in multirooted teeth represents one of the most demanding therapeutic challenges in periodontics. Furcation therapy includes various treatment modalities like either maintenance or elimination of furcation or increased access to furcation area. Recent treatment modalities include regenerative procedures like placement of different type of bone grafts with nonabsorbable or absorbable barrier membranes, through guided tissue regeneration. This study compared the clinical efficacy of nonabsorbable barrier membrane with absorbable membrane when used with hydroxyapatite bone graft (G-Graft) in grade II buccal furcation defects in mandibular 1st molars. Materials and methods: Fourteen subjects with bilateral grade II buccal furcation defects in lower 1st molars were selected and treated in a split-mouth design. After phase I therapy, molars were divided randomly into two groups for the treatment with either resorbable or nonresorbable membrane in conjunction with G-Graft in both groups. Results: All the clinical parameters recorded showed statistically significant improvement in both the groups but no significant difference between two groups was observed. Conclusion: Both nonabsorbable and absorbable barrier membranes were equally effective in treating grade II buccal furcation defects in lower molars when used in conjunction with G-Graft except with respect to horizontal bone fill in which absorbable barrier membrane showed better results.